STRATEGI POLITIK HIZBUT TAHRIR DALAM MENEGAKKAN KHILAFAH ISLAM DI INDONESIA - Manik, Edi Sabara; Hasanuddin, Hasanuddin; Saeri, M. (Jurnal Kebijakan Publik, 2016)
Political Strategy Hizbut Tahrir in Establishing Khilafah Islam in Indonesia. Hizbut Tahrir(HT) as ideology contradict with the government ideology “Pancasila”, but not in policy organization.This proved began 33 years ago until now there is no conflict between Hizbut Tahrir members andgovernment or another Islamic organization. Furthermore, HT built 36 district level and 315 local level.Objective of this study is strategy of Hizbut Tahrir to build the Islamic Caliphate in Indonesia, byusing qualitative descriptive an exploratory approach. This study used 4 members of HT and 2 personacademics with data collection, interview and documentation. The political strategy of Hizbut Tahriris inclusive by recruitment all people in all level such technocrats, students, academics, scientist andulama even more businessman that receive the ideas. The strategy dakwah of HT is extra parliamentarythat used cultural approach and political structure that different to another Islamic organization. Moreever HT pressure a good relation to government until recognized by missive as the organization notforbidden by Ministry of internal affairs (KEMENDAGRI) and Kesbangpol RI.